Hubungan Diplomatik Korea Selatan dengan Indonesia melalui Sektor Korea International Cooperation Agency (KOICA) - Jessika, Hanna; Lubis, Flori Mardiani (Peneliti.net, 2025)
Diplomacy is an activity or art of negotiating that is usually carried out by a representative in one country (diplomat), or an organization. Diplomacy is usually related to international relations engaged in socio-cultural, economic, and trade fields. One of the countries that often conduct diplomatic activities is South Korea. South Korea conducts diplomatic activities with the Indonesian state in the field of education, this is realized in the KOICA organization. KOICA is the Korea International Cooperation Agency, a South Korean-owned international agency that develops developing countries that intend to advance education in their country. Assistance provided in the form of cooperation programs, funds, and others. In particular, Korea has achieved a unique experience in which it has grown from one of the poorest countries in the world to one of the most economically advanced. This is indicated by the entry of Korean entered the OECD/DAC (Development Assistance Committee) on 25 November 2009. The knowledge and experience Korea gained from this transition is a valuable asset that enables KOICA to efficiently support the sustainable socio-economic development of developing countries. Partner countries and offer them hope for a better world..